2021
DOI: 10.1097/md.0000000000025930
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological characteristics of hand, foot, and mouth disease in China

Abstract: Background: To study the epidemic features of hand-foot-mouth disease (HFMD) in mainland China through systematic review and meta-analysis so as to provide evidence for the future prevention and control of HFMD. Methods: Articles on the epidemic features of HFMD in mainland China, written in English or Chinese and released between January 1, 2015 and January 1, 2020, were searched from English literature databases including Embase, Web of Science, PubMed, Cochrane libra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 18 publications
9
22
0
Order By: Relevance
“…And CV-A16 infection reduced as the EV-A71 vaccine could enhance people's immunity against CV-A16 viruses to some extent. 10 The prevalence of CV-A16 showed obvious periodic fluctuations in Beijing from 2010 to 2018, with the detection rate increasing every other year. 11 Nonetheless, in recent years, CV-A6-associated HFMD outbreaks 12,13 and the overall trend of the epidemic of CV-A6-associated HFMD was increasing in China.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…And CV-A16 infection reduced as the EV-A71 vaccine could enhance people's immunity against CV-A16 viruses to some extent. 10 The prevalence of CV-A16 showed obvious periodic fluctuations in Beijing from 2010 to 2018, with the detection rate increasing every other year. 11 Nonetheless, in recent years, CV-A6-associated HFMD outbreaks 12,13 and the overall trend of the epidemic of CV-A6-associated HFMD was increasing in China.…”
Section: Introductionmentioning
confidence: 97%
“…CV‐A16 associated HFMD usually present mild symptoms that resolve within a few weeks. And CV‐A16 infection reduced as the EV‐A71 vaccine could enhance people's immunity against CV‐A16 viruses to some extent 10 . The prevalence of CV‐A16 showed obvious periodic fluctuations in Beijing from 2010 to 2018, with the detection rate increasing every other year 11 …”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that latitude will affect the incidence of HFMD to a certain extent, and the incidence of HFMD is higher in low latitudes such as tropical and temperate regions [ 18 ]. Mainland China spans multiple temperature zones.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of HFMD in southern China is higher than that in the north, and there are two peaks (summer and autumn) of HFMD each year in southern China, while there is only one peak(summer) each year in northern China [ 1 ]. Natural and social factors vary greatly between the south and north, coastal and inland areas, and the prevalence patterns of HFMD are different in different regions [ 18 , 19 ]. Previous studies have found that precipitation, relative humidity, temperature, gross domestic products (GDP), and the population density are the main factors affecting the incidence of HFMD in China [ 20 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of HFMD also varies with season, weather, countries and other factors [ 12 ]. The incidence of HFMD is relatively high in tropical and temperate zones [ 13 ]. The majority of HFMD outbreaks are reported in some Asian-Pacific region countries such as China, India, Malaysia [ 14 ].…”
Section: Introductionmentioning
confidence: 99%